Kompetensi Sumber Daya Manusia dan Impementasi Sistem Keuangan Desa dan Akuntabilitas Pengelolaan Dana Desa - Ardianti, Putu Ayu Ratih; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p10, 2020)
The purpose of this study was to determine the effect of human resource competencies and village financial systems on the accountability of village fund management in Badung Regency. This research was conducted in villages in Badung Regency using a sample of 126 respondents consisting of Village Heads, Village Secretaries, Treasurers and Section Heads, with probability sampling technique with proportionate stratified random sampling method. Data collection was carried out through questionnaires. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that human resource competence has a positive effect on village fund management accountability. The village financial system has a positive and significant effect on the accountability of village fund management. Keywords: Competence; Village Financial System; Accountability.